Development of the Applied Mindfulness Process Scale as a Process Evaluation Measure for Mindfulness Practice in a Chinese Context - Jia, Yitong; Yan, Yitian; Shi, Wen-Xin; Meng, Ge; Zhuang, Xinqi; Zhang, Yin-Ping (Frontiers in Psychology, 2022)
With the rising popularity of mindfulness practice, it is necessary and crucial to evaluate mindfulness using comprehensive and objective measures. The instruments to assess mindfulness in China mainly evaluate mindfulness as a state or trait mode. Few process measures have been developed to clarify effective therapy benefits of the alterations obtained using mindfulness practice. Therefore, this study aims to adapt the Applied Mindfulness Process Scale (AMPS) into Mandarin and explore in detail the reliability and validity of this novel-translated measure. Following cross-cultural modification for original AMPS into Mandarin as per established guidelines, psychometric evaluation was performed on a cohort of 234 Chinese adults. Construct validity was analyzed through exploratory factor analysis (n=115), together with confirmatory factor analysis (n=119). Reliability was assessed by internal consistency together with test-retest reliability. Findings indicated that the internal consistency was high, with Cronbach's alpha being 0.936. The principal component analysis led to a three-factor structure that explained 67.374% of all variations. The three-factor model was consistent with the original scale model. Based upon confirmatory factor analyses, all fitting indices satisfied the standard, which showed a close fit to the data. Therefore, the newly multi-culturally modified AMPS has sufficient validity, test-retest reliability, together with internal consistency. Chinese AMPS may offer researchers and clinicians a psychometrically-optimized tool for evaluating the application of mindfulness and change process within mindfulness-based interventions (MBIs) in Mainland China.